Terror versus soul: The struggle for creativity in primary Initial Teacher Education. (May 2018) - Raymond, Peter
Creativity is a commonly used word in education circles, yet it is also seen as something that is being undermined by contemporary agendas of standards, testing and an increasingly strong focus on core subjects that are used as indicators of school performance, which are impacting the work of teachers. This paper starts from Ball's 2006 paper 'The Teacher's Soul and the Terrors of Performativity' and argues the importance of developing strong senses of identity and agency in student teachers as part of the teacher's 'soul', as a positive response to the pressures, or 'terrors' of a performative, standards based agenda. Having discussed the background of creativity and performativity, the relationship between identity, agency and creativity is explored through the lenses of three theoretical perspectives; Bourdieu and his idea of habitus; Foucault and his ideas about power, discipline and subjectivity; Lacan and Ruti and perspectives from psycho-analysis, foregrounding the notion of 'lack'. In the discussion of this sequence of perspectives, the argument is for a trajectory in which the view of the human subject becomes less deterministic and more agentic. The paper is framed within a virtues ethic and in applying Noddings' (2003) argument, creativity can be seen not so much as a virtue in itself, but the confident and agentic working out of creativity in practice allows educators to work virtuously within a performative culture and with an 'ethical commitment' to creativity.